2011
DOI: 10.1007/s13577-011-0023-2
|View full text |Cite
|
Sign up to set email alerts
|

The enormous influence of TNIK knockdown on intracellular signals and cell survival

Abstract: Basic cellular activities and coordinated cell actions are governed by intracellular signals, among which the Wnt signaling cascade plays an important role in tissue polarity and cell adhesion or movement through the activation of c-Jun N-terminal kinase (JNK) pathway. As one of the central transcriptional factors, Traf2- and Nck-interacting kinase (TNIK) mediates the transactivation of Wnt target genes and promotes the activity of c-Jun N-terminus kinase (JNK)2 when overexpressed. To further understand the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…However, TNIK is a multifunctional protein1920, and its function is not limited to regulation of Wnt signalling or colorectal carcinogenesis. Recently, amplification of TNIK has been reported in 7% (8/106) of gastric cancer patients47.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, TNIK is a multifunctional protein1920, and its function is not limited to regulation of Wnt signalling or colorectal carcinogenesis. Recently, amplification of TNIK has been reported in 7% (8/106) of gastric cancer patients47.…”
Section: Discussionmentioning
confidence: 99%
“…Here we report the development of a novel small-molecule TNIK inhibitor having anti-Wnt and anti-cancer stem cell activities. TNIK has various functions other than regulation of Wnt signalling1920. We therefore initiated this study by developing Tnik -deficient mice to confirm the safety and feasibility of TNIK targeting.…”
mentioning
confidence: 99%
“…Conversely, several studies have demonstrated the reciprocal regulation between TNIK and the JNK/c-Jun signaling pathway (51)(52)(53), where TNIK is essential for activation of the JNK pathway via JNK1 and JNK2. We therefore hypothesized the existence of a positive feedback loop where the WBP2-induced TNIK expression leads to the reciprocal activation of JNK and c-Jun, which in turn further up-regulate its own expression.…”
Section: Wbp2 Primes Wnt Response In Tnbc Wbp2 May Trigger a Positivementioning
confidence: 99%
“…TNIK is a multifunctional protein with serine-threonine kinase and scaffold domains [55] and is considered to be involved in cellular functions other than Wnt signaling [56]. TNIK was originally identified as a new member of the Germinal Center Kinase (GCK) family by Fu et al [57].…”
Section: Other Functions Of Tnikmentioning
confidence: 99%
“…Aminothiazole-based TNIK inhibitors have been shown to exhibit strong anti-tumor activities. Considering the diverse functions of TNIK [56], the targeted activities may not be limited to Wnt signaling, or indeed to colorectal cancer.…”
Section: Expert Opinionmentioning
confidence: 99%